2009
DOI: 10.3928/00989134-20091001-03
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on Photographs: Exploring First-Year Nursing Students' Perceptions of Older Adults

Abstract: Nursing students' exposure to clinical placements with older adults is instrumental in helping them adopt positive attitudes toward care of that population. This qualitative pilot study analyzed perceptions and expectations of a group of first-year students prior to a clinical placement with older adults. A photo-elicitation technique, involving viewing of realistic photographs of older adults being cared for, was used to help students clarify expectations. This was followed by thematic analysis of their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Discussing disparate representations of self-management provided participants an opportunity to critically reflect on their DSM. These findings align with existing evidence that demonstrates that reflecting on photographs in educational and research settings enhanced self-awareness of one's own thoughts and actions (Brand & McMurray, 2009; Linz, 2011; Lorenz, 2011; Pellico, Friedlaender, & Fennie, 2009). Moreover, for some of the participants, self-reflection prompted them to make further changes to aspects of their DSM.…”
Section: Discussionsupporting
confidence: 88%
“…Discussing disparate representations of self-management provided participants an opportunity to critically reflect on their DSM. These findings align with existing evidence that demonstrates that reflecting on photographs in educational and research settings enhanced self-awareness of one's own thoughts and actions (Brand & McMurray, 2009; Linz, 2011; Lorenz, 2011; Pellico, Friedlaender, & Fennie, 2009). Moreover, for some of the participants, self-reflection prompted them to make further changes to aspects of their DSM.…”
Section: Discussionsupporting
confidence: 88%
“…Multimedia including use of visual methodologies in digital storytelling was found to stimulate reflection learning in medical students 41. Images of older adults were found to evoke emotional responses and foster critical reflection in a nursing education study of photo elicitation 42. The combination of viewing paintings and writing a short story to enhance understanding of human suffering has been successfully implemented in workshops for healthcare providers and medical educators 43.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the experimental and experiential educational approaches most welcomed by students in our study were those that enabled students to physically or figuratively practice dignity in care through role play/simulation, patient experience, case studies/scenarios and empathy exercises, rehearsing clinical situations they may encounter in practice to steel their resolve to ensure that they delivered dignity in care and stand up to situations where standards of dignity fell short of those expected by patients. Thus, while our study has confirmed that the experiential and experimental educational approaches that have been used in nurse education to date (Raholm, 2008;Brand and McMurray 2009;McGarry and Aubeeluck 2013;Goodman 2013) are welcomed by students, it goes one step further and suggests that these approaches are vital to guard against the perceived loss of conceptual confidence and practical competence around dignity that (potentially) comes after qualification once students are working in not always positive practice environments. Our findings also suggest that students could be given the opportunity, through the use of such diverse, critique-based educational approaches to engage with the complexities of human dignity.…”
mentioning
confidence: 78%
“…Over the past two decades a range of experiential and experimental educational approaches have been used to challenge student nurses' knowledge and understanding of the concept of dignity and practice of dignity in care, including: patient narratives (Raholm, 2008), photo-elicitation (Brand andMcMurray 2009), drama (McGarry andAubeeluck 2013) and discussion (Goodman 2013). This shows that nurse educators believe that dignity as a concept and dignity in care as a practice are amenable to education.…”
Section: Introductionmentioning
confidence: 99%